Brain near-infrared study of upstairs movement after anterior cruciate ligament reconstruction - Cao, Ziyuan; Zhang, Hao; Wu, Xipeng; Zhang, Yuxuan; Yu, Jiangli; Li, Wei (Frontiers in Neurology, 2025)
ObjectiveAfter anterior cruciate ligament reconstruction (ACLR), patients undergo specific changes in body and specific brain functions, which stem from neuroplasticity. In this study, we employed functional near-infrared spectroscopy (fNIRS) to investigate the characteristics of brain activation in patients after ACLR during a repetitive upstairs task, and compared them with healthy individuals. We aimed to provide a new theoretical basis for the changes in brain function after ACLR and neurorehabilitation of sports injuries.MethodsA total of 27 patients who undergoing right ACLR and 27 healthy controls participated in the study. We utilized fNIRS to collect hemodynamic data from the frontal and parietal cortices of both groups during a repetitive upstairs task. The Lysholm scale assessment was conducted prior to the commencement of the task. Compare the functional characteristics of the brain in post-operative patients and healthy subjects during upstairs tasks, and examine the functional differences between the two groups.Results(1) Patients undergoing ACLR demonstrated a significant negative change in β-value for Channel 25 (t = 4.0461, p = 0.0067) during the repetitive upstairs task. (2) In contrast, the healthy control group exhibited a significant increase in β-value across Channel 6 (t = −3.0489, p = 0.0066), Channel 7 (t = −4.5723, p = 0.0002), Channel 8 (t = −3.0089, p = 0.0072), Channel 13 (t = −2.8789, p = 0.0096), Channel 20 (t = −3.4200, p = 0.0029), and Channel 33 (t = −2.6974, p = 0.0143) during the task. (3) When compared to the healthy control group, ACLR patients exhibited a significant negative change in β-value for Channel 25 (t = 2.7583, p = 0.0089), and Channel 33 (t = 3.0618, p = 0.0040).ConclusionPatients with ACLR exhibited a significant negative activation in a specific brain region during upward stair movements. In contrast, healthy individuals demonstrated activation in two particular brain areas during the same task. Interventions targeting these brain regions may represent a novel rehabilitation approach. This provides a theoretical basis for incorporating fNIRS into the rehabilitation assessment of patients undergoing ACLR. In conclusion, this study provides a theoretical framework for potential interventions and assessments of brain regions following ACLR.